Efficacy of a multicomponent binding agent against combined exposure to zearalenone and ochratoxin A in weaned pigs - Tassis, Panagiotis; Raj, Jog; Floros, Dimitrios; Mittas, Nikolaos; Ntarampa, Niki; Farkas, Hunor; Polizopoulou, Zoe; Vasilievic, Marko (Frontiers in Veterinary Science, 2024)
Introduction The study aimed to evaluate the efficacy of a novel multicomponent substance against combined exposure to the mycotoxins zearalenone (ZEN) and ochratoxin A (OTA) in weaned piglets. Methods In total, 60 piglets at the age of 28 days were equally allocated to four experimental groups (A–D), consisting of eight female and seven male piglets each (15 animals per group, for a total trial duration of 42 days). Animals from group A received typical weaner feed without mycotoxins or the test product [multicomponent mycotoxin detoxifying agent (MMDA)]. Group B animals received the same weaner feed contaminated with 0.992 mg ZEN/kg feed and 0.531 mg OTA/kg feed without the addition of the MMDA. Animals in group C received the same contaminated feed as group B with the addition of 1.5 g MMDA/kg feed, whereas group D received the same feed as group B with the inclusion of 3 g MMDA/kg feed. Clinical signs and performance parameters [body weight (BW), average daily weight gain (ADWG), and feed conversion ratio (FCR)] were evaluated, while mycotoxin residues were also assessed in the liver and kidney tissues. Results Findings showed improved FCR in the group that received the greatest dose of the test product (3 g MMDA/kg feed) compared to the group that received the lower dose (1.5 g MMDA/kg feed). A few hematological and biochemical parameters were slightly altered, predominantly within normal limits. The residue analysis demonstrated a reduction of OTA in liver samples, a-ZEL in the liver and total tested samples, and a total of ZEN and metabolite contents in all samples of the group that received the greatest MMDA dose in comparison to the group that received the toxins without the addition of the test product. Discussion Therefore, a positive effect of the MMDA at the greatest dosage regime on reducing bioavailability and tissue deposition of ZEN and OTA, with a particularly positive effect on FCR in weaned pigs, is suggested under concurrent ZEN and OTA exposure in vivo.